Determination of Cd, Cr, Cu, Ni, Zn in River Fish by Ultrasound Assisted Extraction-Atomic Absorption Spectrometry - Gu, J.L.; Zhao, G. (Asian Journal of Chemistry, 2013)
The conditions for determining heavy metals in river fish through ultrasound assisted extraction were optimized and a method of ultrasound assisted extraction-atomic absorption spectrometry was established for the determination of Cd, Cr, Cu, Ni and Zn present in fish. By ultrasound extraction, quantitative recoveries were reached for all of these five heavy metals investigated, recoveries were found to be 91-110 %. Good linearity of the calibration curves was obtained for all the five elements (r = 0.9936-0.9998). The detection limits of the method were in the range of 0.003-0.010 mg/L and the relative standard deviations were in the range of 1.3-5.7 %. The GBW08573 standard reference material was determined under the optimum experimental conditions by both ultrasound extraction and wet digestion. Results obtained by these two methods are close to each other and in good agreement with the reference values.